The Journey of GOJEK: Becoming Indonesia's First Decacorn Startup - Dzulfikar Ahmad Furqon (Wakil Rektor 3, Direktorat Riset, Publikasi dan Inovasi, Universitas Teknologi Sumbawa, 2023)
This paper centers on the strategic analysis of PT GOJEK Indonesia to establish itself as the leading decacorn company in Indonesia. PT GOJEK Indonesia, headquartered in Jakarta, is a digital payment technology company and multi-service on-demand platform. Initially founded as a contact center in the early part of 2009, Gojek facilitated connections between consumers and courier delivery businesses, alongside the acquisition of two-wheeled vehicles. In 2015, Gojek launched its application with a limited range of services and has since experienced rapid growth. Presently, GOJEK is available in 50 cities across Indonesia. This study provides a concise overview of the company's vision and mission. Various analytical tools, including PESTEL analysis and Porter's Five Forces, are employed to identify the current external factors affecting the company. The VRIO analysis is utilized to assess the internal variables that influence the company's customers. Furthermore, the Blue Ocean Strategy is employed to discuss GOJEK 's generic strategy for its ride-hailing services, while the SWOT analysis is used to analyze the company's overall strengths, weaknesses, opportunities, and threats. The analysis results reveal that Gojek has a significant impact on the political landscape, contributing Rp. 1.7 trillion to the Indonesian economy and promoting digital transactions as a means to reduce air pollution. GOJEK, as the market leader in Indonesia, does not face significant competition concerns. Additionally, Gojek offers unique features that distinguish it from its competitors. Overall, the VRIO analysis demonstrates that Gojek possesses considerable value, particularly due to its exclusive services such as Go-pay, its e-money platform, which enables users to purchase and utilize GOJEK’s services. Based on the SWOT analysis, Gojek exhibits substantial strength and opportunities, indicating its potential to become a preeminent decacorn company in Indonesia.